Breaking barriers: The link between stronger IPRs and trade in services - Olena Ivus (Centre for International Governance Innovation (CIGI), 2024)
As innovation becomes more prevalent and systematically integrated into service industries, service firms increasingly turn to intellectual property rights (IPRs) as a means of safeguarding their intellectual assets. The reliance on these legal rights becomes even more pronounced when service companies endeavour to expand their global reach and tap into international markets where the protection of IPRs is relatively weak, and imitation is more widespread. Disparities in the level of IPRs protection and enforcement across countries can pose significant barriers to cross-border trade and investment in service sectors where the safeguarding of intellectual property (IP) is fundamental. The risk of IP infringement and the limited protection afforded to patents, copyrights and trademarks in certain countries can discourage the expansion of businesses into these markets, limiting the overall growth and accessibility of services in those areas. This paper studies the relationship between trade in services and the strength of IPRs protection at the international level. More specifically, it uses data for 94 countries over the period of 1990-2010 to put forward new empirical evidence about the impact of global strengthening of IPRs protection on cross-border trade in services.
Keywords: 330